Reorganizacija ministarstava u vladi Federacije Bosne i Hercegovine prema srodnosti upravnih poslova i standardima EU / Reorganization of Ministries in the Federation of Bosnia and Herzegovina Government According to the Administration Similarity and EU Standards - Ajanović, Enver (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
Up to the moment, there have been several public administration reforms in Bosnia and Herzegovina. The first time after gaining political independence in 1992 it happened as the result of the Washington Treaty of 1994. This international agreement legally obliged RBiH to establish cantonal authorities at one part of its territory through the Constitution of the FBiH. Therefore on the basis of the B&H Constitution and the Constitutional Court of BiH Decision, the federal government is reformed in accordance with the FBiH Constitution, so there are 16 ministers in the FBiH Government - eight Bosniaks, five Croats and three Serbs. In addition to constitutional changes, as a legal basis for the federal administration reform, the FBiH Parliament first confirmed the Decision of the Higher Representative on the Law on the Federal Ministries and other bodies of the federal administration in 2002. This law has been amended six times. In all of these amendments, there has not been a single reform of administrative organizational rights at the federal level in accordance with the legal standards of the European Union. In accordance with the hierarchical relationship of international and national laws, the Treaty on the EU functioning affects a particular administrative organizational law in member states. By applying those regulations, Ministries of Agriculture, Forestry and Water Management, Environment and Tourism, Culture and Sports and the Ministry of Development, Crafts and Entrepreneurship can no longer exist in the FBiH. The reform of this part of administrative law must have five new ministries: culture, environment, agriculture, sport and tourism. Due to the constitutional provisions in force on the FBiH competencies and that there must be 16 ministries in the FBiH Government; there are currently no conditions for the separation of tourism from environment. It is now possible to set up the Ministry of Agriculture, and in the future it will be necessary to separate the environment and tourism affairs and enact the law so the separated Ministries, as soon as the conditions for such reform of administrative organizational rights at the federal level of government are met.